Effectiveness of Acid-Activated Oil Palm Fiber and Quartz Sand Adsorbents in Reducing Wastewater Pollutant Parameters - Hari Ananda Syahputra Siregar; Rafael remit Winardi (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
Abstract: Palm oil mill wastewater contains high concentrations of organic pollutants and suspended solids that may degrade environmental quality if discharged without proper treatment. This study evaluated the effectiveness of acid-activated oil palm fiber and quartz sand as column adsorbents for improving wastewater quality. The experiment employed a quantitative laboratory approach using a completely randomized design with three adsorbent ratios, namely 1:1, 1:2, and 1:3, each with three replications. The observed parameters included total suspended solids (TSS), total dissolved solids (TDS), color, biochemical oxygen demand (BOD), chemical oxygen demand (COD), and pH. The results showed that the adsorbent column was highly effective in reducing color and moderately effective in lowering BOD and COD, but it increased TSS and TDS. The best color removal was obtained at the 1:2 ratio with a final concentration of 22.00 TCU and an efficiency of 92.93%. The greatest BOD reduction occurred at the 1:3 ratio with a final concentration of 41.03 mg/L and an efficiency of 66.15%, while the best COD reduction was observed at the 1:1 ratio with a final concentration of 233.53 mg/L and an efficiency of 23.63%. The pH increased from 4.81 to 8.34-9.09 after treatment. ANOVA indicated that adsorbent ratio significantly affected BOD and COD, but did not significantly influence TSS, TDS, color, or pH. These findings suggest that acid-activated oil palm fiber and quartz sand have potential as alternative adsorbent media for palm oil mill wastewater treatment, particularly for color and biodegradable organic load removal.